Omalizumab-A review - Kiran Godse; Aayushi Mehta; Sharmila Patil; Manjyot Gautam; Nitin Nadkarni (Wolters Kluwer Medknow Publications, 2015)
Omalizumab is a recombinant, humanized, monoclonal antibody against human immunoglobulin E (IgE). The US FDA has approved this molecule for chronic urticaria.